2019
DOI: 10.3389/fimmu.2019.01872
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the NLRP3 Inflammasome Pathway by Prokineticin 2 in Testicular Macrophages of Uropathogenic Escherichia coli- Induced Orchitis

Abstract: Infections of the reproductive tract are known to contribute to testicular inflammatory impairment, leading to an increase of pro-inflammatory cytokines such as IL-1β, and a decline in sperm quality. Prokineticin 2 (PK2), a secretory protein, is closely associated with the secretion of pro-inflammatory cytokines in inflamed tissue. It was reported that increased PK2 is related to the upregulation of IL-1β, but the underlying mechanism remains elusive. Here, we illustrated that PK2 was upregulated in testicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…LPS and bacterial DNA directly stimulate the upregulation of PK2 in Raw 264.7 cells (34). After UPEC infection, PK2 induces the activation of the NLRP3 inflammasome through the MAPK pathway, thereby promoting the maturation of IL-1b (12). This finding is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…LPS and bacterial DNA directly stimulate the upregulation of PK2 in Raw 264.7 cells (34). After UPEC infection, PK2 induces the activation of the NLRP3 inflammasome through the MAPK pathway, thereby promoting the maturation of IL-1b (12). This finding is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…the NLRP3 inflammasome (12). Despite that NLRP3 and inflammation-related IL-1b are upregulated in UPEC-infected TM, whether CaSR induces NLRP3 inflammasome activity in the pathogenesis of orchitis is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PROK2 is upregulated in granulocytes and macrophages found in inflamed tissue (44). Previous studies suggest that PROK2 plays important roles in mediating inflammation-associated disorders, such as inflammatory pain, psoriasis, and orchitis (44)(45)(46). Choke et al also found that PROK2 was upregulated with 7-fold at rupture sites of AAA (47).…”
Section: Discussionmentioning
confidence: 97%